Innate immune activation in vitiligo: mechanisms and pathophysiological implications - Wang, Yuting; Cao, Junhua; Liu, Xiaomin; Xiong, Chengcheng; Xu, Da; Bian, Fang (Frontiers in Immunology, 2025)
Vitiligo is an autoimmune disease characterized by the progressive destruction of epidermal melanocytes, leading to skin depigmentation. Although significant advances have been made in understanding the pathogenesis of vitiligo, the intricate interplay between genetic predisposition, environmental factors, oxidative stress, and immune dysregulation remains inadequately understood. In particular, increasing evidence highlights the pivotal role of innate immune activation in initiating and amplifying the adaptive immune response, particularly the activation of autoreactive CD8+ T cells, which are the ultimate effectors of melanocyte destruction. However, current therapeutic approaches offer limited efficacy in modulating this pathway. This review provides a comprehensive analysis of the mechanisms driving innate immune activation in vitiligo, with a particular focus on damage-associated molecular patterns (DAMPs), oxidative stress, and key innate immune cells, including dendritic cells (DCs), natural killer (NK) cells, and innate lymphoid cells (ILCs), and their crucial role in bridging innate and adaptive immunity. We further explore how these factors initiate and sustain an inflammatory cascade that bridges innate stress responses with adaptive immune activation, ultimately exacerbating melanocyte destruction. By synthesizing recent advances, we aim to elucidate the critical role of innate immunity in shaping disease progression and discuss emerging innate immune-targeted therapeutic strategies. Understanding these pathways may open new avenues for more effective and targeted interventions in vitiligo treatment.